Early Drain Removal is Safe in Patients With Low or Intermediate Risk of Pancreatic Fistula After Pancreaticoduodenectomy: A Multicenter, Randomized Controlled Trial. Issue 2 (February 2022) - Dai, Menghua; Liu, Qiaofei; Xing, Cheng; Tian, Xiaodong; Cao, Feng; Tang, Wenbo; Lv, Shaocheng; Ma, Yongsu; Zhang, Dongxin; Kleeff, Jorg; Yang, Yinmo; Liu, Rong; et al.
Abstract : Objective: This multicenter randomized controlled trial was designed to test the hypothesis that early drain removal (EDR) could decrease the incidence of grade 2 to 4 complications for patients undoing pancreaticoduodenectomy (PD) with low or intermediate risk of postoperative pancreatic fistula (POPF). Background: The safety and effects of EDR on postoperative complications after PD are still controversial. Methods: A multicenter randomized controlled trial at 6 tertiary referral hospitals was carried out (NCT03055676). Patients who met the inclusion criteria, including drain amylase level less than 5000 U/L on postoperative day (POD) 1 and POD 3, and drain output less than 300 mL per day within 3 days after surgery, were enrolled. Patients were then randomized to the EDR group or the routine drain removal (RDR) group. In the EDR group, all drainage tubes were removed on POD3. In the RDR group, drainage tubes were removed on POD 5 or beyond. Primary outcome was the incidence of Clavien-Dindo grade 2 to 4 complications. Secondary outcomes were comprehensive complication index, grade B/C POPF, total medical expenses and postoperative in-hospital stay etc, within 90 days after surgery. Results: A total of 692 patients were screened, and 312 patients were eligible for randomization. Baseline characteristics were well balanced between the 2 groups and 96.8% of these 312 patients had low or intermediate risk of POPF, according to the 10-point fistula risk score. A total of 20.5% of the patients in the EDR group suffered at least 1 grade 2 to 4 complication, versus 26.3% in the RDR group ( P = 0.229). Multi-variate analysis showed older age (>65 years old) and blood transfusion were independent risk factors for grade 2 to 4 complications. The rate of grade B/C POPF was low in either group (3.8% vs 6.4%, P = 0.305). The comprehensive complication index of the 2 groups was also comparable (20.9 vs 20.9, P = 0.253). Total medical expenses were not significantly different. Postoperative in-hospital stay was clinically similar (15 days vs 16 days, P = 0.010). Conclusions: Nearly half of the patients undergoing PD met the inclusion criteria, predicting low incidence of grade B/C POPF and major complications. EDR was safe in these patients but did not significantly decrease major complications. Abstract : Supplemental Digital Content is available in the text